Effect of Radon Concentration in Air on the Quality of Radioactivity Measurements in the Human Body - Valakis, S.; Pallada, S.; Potiriadis, C.; Kolovou, M.; Stamatelatos, I. E.; Kalef-Ezra, J. (HNPS Advances in Nuclear Physics, 2012)
A prototype shadow-shield whole body counter is used at the University of Ioannina Medical Physics Laboratory as a tool in radiation protection and in biomedical research. In this study the effect of natural airborne radioactivity on the measurement quality features was investigated and performance improvements were developed. Radon air concentration in the counting room was assessed using electret and track detectors over short and long time periods, respectively under various ventilation conditions. A method based on the assessment of the 214Bi 1.76 MeV spectral region was developed to correct for the interference of the radon products to the lower energies of the spectrum. Moreover airborne radioactivity in the counting room was controlled by forced ventilation. Double measurements were carried out in anthropomorphic phantoms and in adult volunteers to assess the impact of the room ventilation module in the measurement precision. Radon control coupled with corrections for the interference of its decay products improved substantially the counter performance characteristics.